Pengaruh Self Efficacy Mobilisasi Terhadap Tingkat Kemandirian Pasien Post Sectio Caesarea Di RS Banyumanik Semarang - Nur Rahimah; Tia Nurhanifah; Kristina Maharani (DIAGNOSA: Jurnal Ilmu Kesehatan dan Keperawatan, 2024)
Introduction: The number of Sectio Caesarea continues to increase throughout the world, with an average Sectio Caesarea delivery rate of 5%–15% per 1000 births in the world. In the Central Java Region in 2018, section caesarean deliveries were 17.10%, and the rest were vaginal deliveries. In post-section Sectio Caesarea, patients have different levels of independence. One form of intervention for increasing maternal independence is self-efficacy mobilization.Objective: The aim of this study was to determine the effect of self-efficacy mobilization on the level of independence of post-section caesarean patients at Banyumanik Hospital. Methods: This type of research was quantitative with a quasi-experimental method using a one-group post-test-only design. Population: The population of this study was all mothers who delivered a caesarean section with uncomplicated spinal anaesthesia. Sampling: The sampling technique used in this study was purposive sampling, with a total sample taken of 30 women post-section caesarean. The instruments used in this study were questionnaires and observation sheets.Results: Data analysis was carried out univariately and bivariately using the normality test, with the results of the data being distributed abnormally (sig <0.05) so that the next test used the non-parametric test, namely the Wilcoxon Test, which showed the results of Zcount > Ztable (4,813 > 1,645) and Asymp values. Sig (0.000) < α (0.05), which means Ho was rejected, means that there is an effect of self-efficacy mobilization on the independence level of post-section caesarean patients at Banyumanik Hospital, Semarang.